A review of the factors affecting the properties of bamboo fiber bio-composite materials / Anith Athierah Aziz, Sallehan Ismail and Siti Akhtar Mahayuddin - Aziz, Anith Athierah; Ismail, Sallehan; Mahayuddin, Siti Akhtar (Universiti Teknologi MARA, Perak, 2023)
The increasing demand for eco-friendly, sustainable, biodegradable natural fiber reinforced composites is a direct result of an increase in environmental awareness and a shift away from traditional material sources that are in favour of composites which derived from renewable green resources. Natural fiber composites have garnered significant interest due to their abundance. Among other advantages, natural fiber composites are inexpensive, biodegradable, and renewable. As a result, bamboo fiber has recently received a great deal of attention, and it has been extensively utilised in the production of bio-composite materials to replace or reduce the use of nonrenewable or synthetic fiber. The quality of bamboo fiber composites is largely determined by factors such as the selection of an appropriate bamboo fiber, preparation and extraction methods, and resin. Inappropriate selection of these factors may have a negative impact on the quality of bamboo fiber composites. Therefore, the purpose of this study is to provide a comprehensive review of these factors, which may aid in the selection process. In this study, the properties of fibers, moisture content, orientation and length of fibers, matrix, and fiber extraction processes are described in detail. Thiese findings can serve as a reference for future research on bamboo fiber composites and promote their use.